2022
DOI: 10.3390/nu14214616
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Food Insecurity and Making Hunger-Coping Trade-Offs during the COVID-19 Pandemic: The Role of Sources of Food and Easiness in Food Access

Abstract: Many individuals make financial, health and food related trade-offs to cope with the challenges of food insecurity and to meet their household needs for healthy, affordable food. A survey (n = 652) was conducted in nine rural counties in South Carolina, USA, during the COVID-19 pandemic from August 2020 to July 2021. We examine if level of food insecurity predicts hunger-coping trade-offs, and whether this relationship is moderated by easiness in food access and dependence on different food source types. Nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Research has explored how people cope with financial hardship generally (Baek & DeVaney, 2010; Edin & Lein, 1997) and food insecurity specifically (Kamdar et al., 2019; Farahbakhsh et al., 2015; Leddy et al., 2020; Gundersen & Garasky, 2012). Some recent research has explored the intersection between food insecurity and financial coping actions (Luo et al., 2022; Niles et al., 2020), but gaps remain in terms of the breadth of actions examined, how these actions configure into strategies and the impact of the severity of food insecurity on the employment of these strategies. Accordingly, the present study empirically identified five categories of coping strategies from 51 possible financial management actions and examined the relationship between the severity of food insecurity and engagement in each strategy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has explored how people cope with financial hardship generally (Baek & DeVaney, 2010; Edin & Lein, 1997) and food insecurity specifically (Kamdar et al., 2019; Farahbakhsh et al., 2015; Leddy et al., 2020; Gundersen & Garasky, 2012). Some recent research has explored the intersection between food insecurity and financial coping actions (Luo et al., 2022; Niles et al., 2020), but gaps remain in terms of the breadth of actions examined, how these actions configure into strategies and the impact of the severity of food insecurity on the employment of these strategies. Accordingly, the present study empirically identified five categories of coping strategies from 51 possible financial management actions and examined the relationship between the severity of food insecurity and engagement in each strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to indicate whether they had taken certain actions “to help manage expenses in the face of rising costs of living” [emphasis included]. The period to which participants were asked to refer when identifying the actions taken was “this year (2022).” The possible actions presented to participants were identified through review of the literature on food insecurity and on general financial hardship to identify household and individual‐level actions taken to cope with each (e.g., Edin & Lein, 1997; Luo et al., 2022; Niles et al., 2020). In addition, media articles reporting on the cost‐of‐living crisis were reviewed to identify actions that were common or resonant enough to warrant public reporting (for example, the dilemma of choosing whether to “heat or eat” and people, particularly young people, combining households; Holmes, 2022; The Guardian, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations